Autogenous dental transplantation in mandible: Clinical case report (Research, Society and Development, 2023)
Autogenous dental transplantation refers to the surgical procedure of implanting a tooth, sourced from the patient's own dentition, into an empty dental socket, whether it is freshly extracted or surgically prepared. This technique serves as a therapeutic alternative for the replacement of essential teeth required for chewing and is particularly indicated in cases of dental agenesis, premature tooth loss due to trauma, periodontal disease, or caries. Molars, given their functional significance, are frequently chosen for this procedure. This study presents a clinical case in which a severely compromised tooth (tooth 46) was extracted, and tooth 38 was transplanted into the corresponding socket, an economically viable option when compared to other forms of rehabilitation. After a six-month follow-up, satisfactory healing at the surgical site and successful integration of tooth 38 into the socket were observed. Through this report and the consulted literature, it is evident that autogenous dental transplantation represents an effective therapeutic option for cases of early tooth loss. It is important to take into account pre-operative and post-operative factors such as the patient's age, stage of root development, the type of transplanted tooth, surgical trauma during extraction, and storage after extraction, as these variables influence the success of the procedure.